The practices and challenges of accelerated educational programs in North Wollo zone, Amhara region, Ethiopia - Shiferaw, Yimer Gobezie; Wedi, Sindew Asmare (Frontiers in Education, 2025)
This study aimed to investigate the practices and challenges of the Accelerated Education Program (AEP) in the North Wollo Zone, with a particular focus on its alignment with Speed School guidelines. The research evaluated core programmatic components such as the implementation of teaching-learning activities, Self-Help Groups (SHGs), and the prospects of the program’s beneficiaries, while also identifying critical barriers affecting its success. A qualitative research approach grounded in the social constructivist paradigm was employed, utilizing a case study design to provide in-depth insight. Data were collected through interviews, focus group discussions (FGDs), observations, and document reviews. A total of 25 key informants participated, including curriculum team leaders, Speed School Program (SSP) focal persons, school directors, supervisors, teachers, and students. Thematic analysis was applied, and results were presented narratively. The study found that both ALFA and adoption classes completed their instructional activities within the prescribed ten-month timeframe, though daily schedules varied by school. Preliminary activities, including stakeholder validation workshops, were conducted at multiple administrative levels. However, the program encountered serious financial limitations such as delayed fund disbursement, insufficient training budgets, and lack of incentives for implementers. Regarding SHGs, 315 out of 375 targeted mothers (84%) participated, contributing to a total savings and project fund of ETB 172,875, which supported small-scale income-generating projects like livestock and poultry production. Teachers noted that SHGs enhanced not only household income but also parent collaboration and engagement in education. The findings highlight both the potential and fragility of the Accelerated Education Program. While the program has demonstrated promising outcomes in community engagement and student reintegration, its long-term success is threatened by funding and coordination challenges. It is recommended that stakeholders view the Speed School as a strategic intervention aligned with national education and development goals. Strengthened partnerships, community dialogue on the importance of education, and the establishment of robust, well-funded social protection mechanisms are critical to sustaining the program and addressing the needs of out-of-school children.